The impact of artificial intelligence on modern education - Serhina, Svitlana (Соціально-гуманітарна науково-творча майстерня "Новий курс", 2024)
The article is devoted to the study of the influence of artificial intelligence on modern education, analyzing the prospects of the application of artificial intelligence in higher education institutions and the problems arising in this process. The author notes that the future of higher education is inextricably linked to the development of information technology and intelligent machines -the prospects of artificial intelligence open new opportunities in teaching and learning in higher education institutions. The author identified the positive aspects of introducing artificial intelligence in education and highlighted the potential risks. The article’s author concludes that higher education institutions need to rethink their functions and pedagogical models of education about artificial intelligence, as there are great opportunities for higher education institutions due to the application of artificial intelligence in the educational process.
Keywords: artificial intelligence; education; higher educational institution; educational sphere; automation; personalized learning; integration